THE EFFECT OF THE THINK-TALK-WRITE (TTW) STRATEGY ON THE ELEVENTH GRADE STUDENTS' DESCRIPTIVE WRITING SKILLS AT SMKS 1 TAMANSISWA PEMATANGSIANTAR - Maretta Kesia Siadari; Bobby Pramjit Singh Dhillon; Siska Situmeang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this research was to determine whether there was a positive and significant effect of the Think-Talk-Write (TTW) strategy on students’ ability to write descriptive texts at the eleventh grade of SMKS 1 Tamansiswa Pematangsiantar. This study employed a quantitative research design. The population of the research consisted of all eleventh-grade students, while the samples were class XI AKL and XI KS. To collect the data the researcher used written test and observation. This research confirmed that students taught using the Think-Talk-Write (TTW) strategy achieved better results than those who were not. The study involved two classes: the experimental class (XI AKL) and the control class (XI KS). The post-test mean score of the experimental class was 75.96, which was higher than that of the control class, which scored 68.52. The result of the independent samples t-test showed a significance value (sig. 2-tailed) of 0.011, which was lower than the significance level of 0.05. Therefore, the alternative hypothesis (Ha) was accepted, and the null hypothesis (Ho) was rejected, indicating a significant difference in students’ post-test scores between the experimental and control classes. The results suggested that schools, teachers, and other researchers should use the Think-Talk-Write (TTW) strategy because it has been shown to effectively improve students’ descriptive writing skills.